Numerical and Experimental Research on Single-Valve and Multi-Valve Resonant Systems - Bai, Changan; Chen, Tianning; Yu, Wuzhou (Frontiers in Materials, 2021)
Multiple valves in the pipeline system belong to obvious periodic structure distribution type. When the high-speed airstream flowed through the pipeline valve, it would produce obvious aero-acoustic and acoustic resonance. The acoustic resonant system with single and six pipe valves were investigated to understand the flow and acoustic characteristics using numerical simulation method and testing method. The strongest acoustic resonance occurred at a specific flow velocity with a corresponding Strouhal number of 0.47 corresponding to the geometric parameters in the paper. Moreover, acoustic resonance occurred in a certain velocity range, rather than increasing with the increase of the velocity of the pipeline. This regular provided important theoretical basis for the prediction of acoustic resonant and ultimate acoustic load of single valve system. When the pipeline attached with multiple valves and the physical dimension was large, the conventional aero-acoustics calculation results were seriously attenuated at high frequency, the calculation method involving cut-off frequency in this paper was presented and could be used to explain the excellent agreement of the SPL below the cut-off frequency and the poor agreement above the cut-off frequency. A new method involving steady flow, and stochastic noise generation and radiation(SNGR) was proposed to obtain better results for the SPL at the middle and high frequencies. The comparison results indicated that the traditional method of Lighthill analogy and unsteady flow could accurately acquire aerodynamic noise below the cut-off frequency, while the new method involving steady flow and SNGR could quickly acquire aerodynamic noise above the cut-off frequency.